Technology of WLAN in Operation Level Based on Metropolitan Area Network - Bo Gao; Yiming Pan; Guojin Huang (Dianxin kexue)
As an extension of the cable broadband network，WLAN is also an important part of the wireless broadband network.In recent years，local governments have put forward the construction of “wireless city”as the fifth city public infrastructure，China Telecom Co.Ltd.also put forward the WLAN construction as the forth basic network.These factors promoted the large-scale construction and development of WLAN.The construction goal and the network architecture of WLAN based on metropolitan area network were analyzed.The networking technologies and the security policy deployment of WLAN were proposed.